Jiannao Pills alleviate depression-like behavior in chronic unpredictable mild stress-induced mice through NF-κB/NLRP3 pathway - Pan, Jia; Liu, Jie; Fan, Qingying; Gao, Shiman; Liang, Yuanyuan; Zhang, Lihan (Frontiers in Pharmacology, 2025)
ObjectiveDepression is a significant mental disorder that damages human health. Jiannao Pills (JNW) as a commercial mediation has demonstrated its effectiveness in depression treatment but the mechanism remains elusive. This research endeavored to examine the effects of JNW on the depression-like behavior in mice subjected to chronic unpredictable mild stress (CUMS) and to elucidate the underlying molecular mechanism.MethodsThe CUMS-induced mice were utilized to evaluate the antidepressant efficacy of JNW. JNW was intragastric administered at the dosage of 0.375, 0.75 and 1.5 g/kg for 32 consecutive days. The following tests were employed to assess depression-like behavior: sucrose preference test (SPT), coat state assessment (CSA), tail suspension test (TST), forced swimming test (FST), and open field test (OFT). The concentrations of Hypothalamic-pituitary-adrenal (HPA) axis hormone, monoamine neurotransmitter and pro-inflammation cytokine was quantified by ELISA. The transcriptional levels of pro-inflammation cytokine, Bcl-2, Bax, NLRP3 and Caspase-1 was assessed by qRT-PCR. The protein expression level of Bcl-2, Bax, NF-κB p65, IκBα, p-IκBα, NLRP3 and Caspase-1 was determined by Western blot.ResultsJNW could significantly enhance the sucrose preference, decrease CSA score, reduce immobility time of TST and FST and improve various aspects of behavior in OFT, including an increase in the number of entries to the central zone, the duration spent in the central zone, and the total movement distance. JNW could also suppress IL-1β, IL-6, and TNF-α production and mRNA expression, and lower the level of CRH in the hypothalamus and ACTH and CORT in the serum, increase the level of monoamine neurotransmitter in both serum and hippocampus, upregulate the mRNA and protein expression of Bcl-2 while downregulate the mRNA and protein expression of Bax. Furthermore, JNW notably suppressed NLRP3 and Caspase-1 mRNA and protein, inhibited the expression of NF-κB p65, and increased phosphorylation and degradation of IκBα.ConclusionJNW could alleviate depression-like behavior in mice subjected to CUMS, and these effects may be mediate through NF-κB/NLRP3 pathway.